2003
DOI: 10.1590/s0004-282x2003000100020
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of pleomorphic xanthoastrocytoma: case report

Abstract: -We report a case of a pleomorphic xantoastrocytoma which manifested itself as a cystic isodense lesion in the right fronto-temporal lobe in a 26 year-old woman. It appeared as a soft yellow tumor with cystic cavities on surgery. Five months after this surgery, the patient was submitted to a new operation, which revealed a friable tumor, easily differentiated from the normal parenchyma, with cystic components. The histopathological examination demonstrated pleomorphic xanthoastrocytoma with malignant transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 9 publications
0
12
0
3
Order By: Relevance
“…Sparse to numerous mitoses in the first specimens were noted by Macaulay et al [11], Bayindir et al [13], and Tonn et al [14]. Lymphocytic infiltration was noted for cases reported by Kepes et al [9], Allegranza et al [10], Macaulay et al [11], Tonn et al [14]and de Tella et al [18]. Once the malignant transformation occurred, the anaplastic PXA cases exhibited both endothelial proliferation [10, 14, 17, 18]and pseudopalisading [10, 11]in addition to necrosis and mitosis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Sparse to numerous mitoses in the first specimens were noted by Macaulay et al [11], Bayindir et al [13], and Tonn et al [14]. Lymphocytic infiltration was noted for cases reported by Kepes et al [9], Allegranza et al [10], Macaulay et al [11], Tonn et al [14]and de Tella et al [18]. Once the malignant transformation occurred, the anaplastic PXA cases exhibited both endothelial proliferation [10, 14, 17, 18]and pseudopalisading [10, 11]in addition to necrosis and mitosis.…”
Section: Discussionmentioning
confidence: 96%
“…Our search revealed 15 fully documented PXA cases that had shown malignant transformation [7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18]. Case 4 of Whittle et al [40], who had an extensive recurrence that took place only 5 months after initial surgery, was not included since a specimen for histological evaluation was not available either from surgery or autopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Anaplastic PAxs are considered when mitosis is > 5/10hpf, necrosis and these are usually recurrence. 7,11 The studies showed 9-20% PAXs may undergo malignant transformation.…”
Section: Figure 2: Numerous Xanthoamatous Foamy Cells and Multinucleamentioning
confidence: 99%
“…Examples of this unusual neoplasm have also been reported in the cerebellum (11,12,14,23,31,35), pineal region (27), sella turcica (2), spinal cord (15,26), and even the retina (40). PXA often arises in adolescents and young adults and is amenable to surgical resection with good disease control (8), although it may harbor the potential for malignant transformation (1, 4, 5,6,9,25,28,30,32,38). To our knowledge, this is the first reported case of a solid PXA located exclusively within the third ventricle, a site not previously described in the literature.…”
Section: Introductionmentioning
confidence: 99%